Subsurface Structure Interpretation of Southern Flank of Tangkuban Parahu Based on Gravity Method - ABDULLAH (NIM: 22315017), HASDI
Tangkuban Parahu is one of strato type volcano which grows in the eastern of Sunda Caldera. Based on the pattern, the eruption is grouped in three phases. The explosive phase that produces pyroclastic and lava, The effusive phase produces many lava flows composed of basaltic andesite, now the volcano is growth phase small explosive, interspersed phreatic sometimes. Therefore, this volcano is interesting to be studied related itÃ‚Â’s geological phenomenon. A subsurface geological research is essential to know the description of subsurface structures such as rocks, fracture, and groundwater encouraging phreatic eruption. Geophysical research use gravity method assessed effectively and efficiently, to know density of subsurface rock can make up Tangkuban Parahu based on gravity anomalies on the surface, so the subsurface geological condition can be prediction by rock density which is known. The research aims to get Bouguer anomalies map, regional anomalies map and residual anomalies map, and subsurface geologycal modelling. There are thirty five gravity observation data of direct acquisition in the field with random pattern spread, from peak to Southern Flank the dominant spread of data toward the Southern Flank. Regional and Residual anomalies separation using the 2D fast fourier transform lowpass filter method. The quantitative interpretation of subsurface geological by forward modelling. This investigation gives better understanding on the subsurface structure of Southern Flank of Tangkuban Parahu Volcano, there are two normal faults, based on cross section A to B and C to D, comonly, there are two units of rock make up Tangkuban Parahu, Consits of old volcano product and young volcano product.